2007
DOI: 10.1007/s11418-006-0130-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of mogrosides in Lo Han Kuo (Siraitia grosvenori) fruits

Abstract: Mogrosides at different growth stages of Lo Han Kuo (Siraitia grosvenori) fruits were analyzed qualitatively and quantitatively using TLC and HPLC. The results show that we can clearly discriminate the seasonal variation of the main mogrosides in Lo Han Kuo fruits: mogroside V is the main constituent of ripe fruits, while mogrosides III and II E are the leading components in unripe fruits. A comprehensive validation (sensitivity, linearity, reproducibility and recovery) of an HPLC method that can simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
(11 reference statements)
2
20
0
1
Order By: Relevance
“…S1B). This observation coincides with data presented in an earlier study of Siraitia fruit that also showed that the total mogroside content did not increase during development (24). Rather, the existing mogroside pool in the immature fruit was progressively glucosylated to the penta-glucosylated form.…”
Section: Resultssupporting
confidence: 92%
“…S1B). This observation coincides with data presented in an earlier study of Siraitia fruit that also showed that the total mogroside content did not increase during development (24). Rather, the existing mogroside pool in the immature fruit was progressively glucosylated to the penta-glucosylated form.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, its contents was in the range of 5.77–11.75 mg/g in ten batches of LHG samples, which were all more than the 5 mg/g set in the Chinese Pharmacopeia . The result is consistent with previous reports that MV was found in a sample of whole fruits of S. grosvenorii at levels of 0.5–1.4% w/w . Then, SI is the second most abundant sweet mogroside in the tested samples and is the sweetest among the mogrosides.…”
Section: Resultssupporting
confidence: 92%
“…Các nghiên cứu gần đây đã chỉ ra rằng, các hợp chất mogroside (glycoside) có trong quả La hán là nguyên nhân làm giảm một số căn bệnh liên quan đến hệ thống hô hấp và tiêu hóa ở người như: chứng tăng huyết áp, bệnh lao, bệnh suyễn, tiểu đường [7]. Nhiều hợp chất mogroside có trong quả La hán đã được phát hiện và tách chiết thành công, trong số đó có mogroside IV và mogroside V chiếm thành phần chủ yếu và có độ ngọt cao nhất [1]. Mặc dù có độ ngọt cao, nhưng chất ngọt trong quả La hán rất khó bị phân hủy bởi enzyme trong cơ thể người, khó hấp thu và chuyển hóa thành năng lượng, vì vậy, khả năng sinh năng lượng thấp [5].…”
Section: Mở đầUunclassified